2016
DOI: 10.1007/s11192-016-2086-z
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the digital footprints to scholarly articles from social media

Abstract: Scholarly articles are discussed and shared on social media, which generates altmetrics. On the opposite side, what is the impact of social media on the dissemination of scholarly articles and how to measure it? What are the visiting patterns? Investigating these issues, the purpose of this study is to seek a solution to fill the research gap, specifically, to explore the dynamic visiting patterns directed by social media, and examine the effects of social buzz on the article visits. Using the unique real refe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This does show that Twitter and Facebook visitors to scholarly articles do result in actual clicks on those publications. (Wang et al, 2016) Wider impact of these practices is not clear at this time. Researchers are analyzing whether the wide dissemination through tweets (by authors or others) and the enhanced visibility that Twitter makes possible does actually affect citation impact, as measured by various new (alternative) metrics.…”
Section: More Public and Social Media Engagement For The Results Of Rmentioning
confidence: 94%
See 1 more Smart Citation
“…This does show that Twitter and Facebook visitors to scholarly articles do result in actual clicks on those publications. (Wang et al, 2016) Wider impact of these practices is not clear at this time. Researchers are analyzing whether the wide dissemination through tweets (by authors or others) and the enhanced visibility that Twitter makes possible does actually affect citation impact, as measured by various new (alternative) metrics.…”
Section: More Public and Social Media Engagement For The Results Of Rmentioning
confidence: 94%
“…Studies of sharing via Twitter, Facebook and Mendeley show at least more attention to openly published articles than those that are published in a closed access manner. (Wang, Fang, & Guo, 2016) Savvy researchers promote and market their scholarly work for greater impact using proven strategies that work with various social media. (Mollett et al, 2017) In a sense, there are methods that any author can use to market a publication, drawing attention to it.…”
Section: More Public and Social Media Engagement For The Results Of Rmentioning
confidence: 99%
“…In a similar fashion, Moed (2005) already found that citations and downloads show different patterns of obsolescence, and about 40% of downloads accumulated within the first 6 months after publication. More recently Wang et al (2016a) using the article-level "usage counts" provided by Web of Science to investigate the usage patterns of indexed papers, identified that newly published papers accumulated more Web of Science usage counts than older papers.…”
Section: Accumulation Patterns and Immediacy Measurement Of Citationsmentioning
confidence: 99%
“…In the era of social media, there are many ways a scientist can promote their work and engage with others Twitter has over 313 million active monthly users and Facebook has over 1.71 billion. Research has shown that social media can increase the number of journal article downloads (Wang et al, 2016& Allen et al, 2013. So why do some academics and research scientists avoid these platforms?…”
Section: Why Should I Engage?mentioning
confidence: 99%